2022
DOI: 10.1063/5.0091192
|View full text |Cite
|
Sign up to set email alerts
|

Transitional flow structures in heated hypersonic boundary layers

Abstract: Transition in a Mach 6 flared cone boundary layer over a heated wall has been investigated in the Mach 6 wind tunnel at Peking University using visualization, focused laser differential interferometry, infrared imaging, particle image velocimetry (PIV), and direct numerical simulation (DNS). The model's wall-temperature ratio [Formula: see text] (where [Formula: see text] and T0 are, respectively, the wall temperature and oncoming stream stagnation temperature) can be controlled to vary from 0.66 to 1.77. An u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…However, further support for the corresponding experiments or full three-dimensional (3-D) DNS was not provided. Zhu et al (2022) also experimentally demonstrated that a nearly adiabatic wall or heated wall enabled the first mode to be comparable to or overtake the second mode in frequency spectra. Under other wind-tunnel conditions, solid experimental evidence of interactions between the second mode and the low-frequency component was presented by Kimmel & Kendall (1991), Bountin et al (2008), Munoz, Heitmann & Radespiel (2014) and Craig et al (2019).…”
Section: Introductionmentioning
confidence: 94%
“…However, further support for the corresponding experiments or full three-dimensional (3-D) DNS was not provided. Zhu et al (2022) also experimentally demonstrated that a nearly adiabatic wall or heated wall enabled the first mode to be comparable to or overtake the second mode in frequency spectra. Under other wind-tunnel conditions, solid experimental evidence of interactions between the second mode and the low-frequency component was presented by Kimmel & Kendall (1991), Bountin et al (2008), Munoz, Heitmann & Radespiel (2014) and Craig et al (2019).…”
Section: Introductionmentioning
confidence: 94%